2009
DOI: 10.1248/bpb.32.220
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Tanshinone IIA on the Early Stage of Experimental Diabetic Nephropathy

Abstract: (TGF-b b 1 ), collagen IV, and monocyte/macrophage (ED-1) either in the serum or kidney were significantly reduced. These results suggest that Tanshinone IIA might have protective effects on several pharmacological targets during the progression of DN, and could be a potential drug for the prevention of DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…The progression of CRF is characterized histologically by progressive glomerulosclerosis and tubulointerstitial fibrosis (9,36). A significant observation of the present study was the marked improvement effect of SKG on renal pathological damage, through inhibition of the relative area of renal glomerulosclerosis and tubulointerstitial fibrosis, particularly in the SKGL and SKGM groups.…”
Section: Discussionsupporting
confidence: 50%
“…The progression of CRF is characterized histologically by progressive glomerulosclerosis and tubulointerstitial fibrosis (9,36). A significant observation of the present study was the marked improvement effect of SKG on renal pathological damage, through inhibition of the relative area of renal glomerulosclerosis and tubulointerstitial fibrosis, particularly in the SKGL and SKGM groups.…”
Section: Discussionsupporting
confidence: 50%
“…Pioglitazone attenuates DN by downregulating TGF-β and NFκB in type II diabetic rats (43). Kim et al (13) identified that TGF-β was decreased in DN rat models treated with TⅡA. In the present study, the results revealed that TGFβ and p65 mRNA and protein expression were upregulated in DN rats and downregulated following treatment with TⅡA.…”
Section: Discussionsupporting
confidence: 62%
“…As a multi-functional agent in TCM, TⅡA has a fundamental role in cellular responses to extracellular stimuli. For example, TⅡA protects cardiomyocytes in part through B-cell lymphoma 2/B-cell lymphoma 2-associated X protein and Akt-signaling pathways (14)(15), is able to produce an inhibitory effect on the sterol regulatory element-binding transcription factor 1 pathway through the phosphoinositide 3-kinase/Akt signaling pathway (16) and significantly inhibits the expressions of numerous factors, including transforming growth factor β (TGFβ), in a rat model of DN (13). However, only the primary action of TⅡA on DN has been studied, and the mechanisms underlying how TⅡA ameliorates DN require further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…Salvianolic acid B was found to have anti-inflammatory, anti-fibrogenic, skip flap ischemia-reperfusion attenuation, atherosclerosis reduction, and cyclooxygenase-2 attenuation properties [6][7][8][9][10], in addition to being an efficient radical scavenger and antioxidant [11]. Likewise, tanshinone IIA is also characterized by anti-inflammation activity, anti-oxidation, and cardio-protection, as well as neuro-protection, anticancer and diabetic nephropathy prevention [12][13][14][15][16][17]. Remarkably, both salvianolic acid B and tanshinone IIA were also found to inhibit atherogenesis hyperlipid activity [18].…”
Section: Introductionmentioning
confidence: 99%